Studi Kompleks Asosiasi Logam Berat Timbal (Pb) dengan Menggunakan KI dan Methyl Green - R, Yoanatul Hasanah; Nasra, Edi; Nizar, Umar Kalmar; Etika, Sri Benti (Periodic, 2023)
The measurement methods in this study used are UV-Vis and AAS ( Atomic Absorption Spectrophotometer). The Pb(NO3)2 solution is dissolved with excess iodide so that it forms a PbI42- anion complex. This anion complex is then reacted with the cationic dye methyl green forming an association complex [PbI4][MG].The result of this study is that the maximum wavelength of the PbI42- anion complex is at 267 nm with stability time of 2 hours. Then the iodide concentration is 0,333 M with an absorbance 0.795 then the maximum wavelength of the association complex [PbI4][MG] is 636 nm at pH 5 and methyl green concentration is 0.00013% and has a concentration factor 20,39 times.